Exenteration for benign orbital disease. - Rose, G E (1994)
Exenteration, or removal of the globe with part or all of the surrounding orbital contents, is generally reserved for malignancy. The procedure may, however, be of value in the management of some benign orbital diseases. The indications for exenteration in management of benign orbital disease are threefold. Firstly, patients in whom diffuse disease, such as idiopathic inflammation, has resulted in an irretrievable situation of visual loss and clinically uncontrollable pain or disfigurement; in many such cases we consider exenteration to be preferable to the (often severe) side effects of prolonged and inadequate medical therapy. The second group are those patients with grossly disfiguring orbital abnormalities, such as teratomas, extensive varices, or massive optic nerve tumours. The last group comprises patients with tumours that, while histologically benign, may have malignant potential or show a tendency to diffuse or persistent infiltration of orbital soft tissues. Sixteen illustrative cases of full or partial exenteration for benign disease are described.